Gyrokinetic investigation of Alfvén instabilities in the presence of turbulence. (27th April 2021) - Biancalani, A; Bottino, A; Di Siena, A; Gürcan, Ö; Hayward-Schneider, T; Jenko, F; Lauber, P; Mishchenko, A; Morel, P; Novikau, I; Vannini, F; Villard, L; et al.
Abstract: The nonlinear dynamics of beta-induced Alfvén eigenmodes (BAEs) driven by energetic particles (EPs) in the presence of ion-temperature-gradient turbulence is investigated, by means of selfconsistent global gyrokinetic simulations and analytical theory. A tokamak magnetic equilibrium with large aspect ratio and reversed shear is considered. A previous study of this configuration has shown that the electron species plays an important role in determining the nonlinear saturation level of a BAE in the absence of turbulence (Biancalani et al 2020 J. Plasma Phys. ). Here, we extend the study to a turbulent plasma. The EPs are found modify the heat fluxes by introducing energy at the large spatial scales, mainly at the toroidal mode number of the dominant BAE and its harmonics. In this regime, BAEs are found to carry a strong electron heat flux. The feed-back of the global relaxation of the temperature profiles induced by the BAE, and on the turbulence dynamics, is also discussed.